# multipling poly

• Jan 20th 2009, 07:32 PM
Leona_Marie
multipling poly
4x^2 -2x +6

x x +3
--------------------
12x^2 -6x 18
4x^3 -2x^2 +6x =
4x^3 8x^2 +0x +18
If -6 +6 =0 Why doesn't x -x =0
• Jan 20th 2009, 07:38 PM
Mush
Quote:

Originally Posted by Leona_Marie
4x^2 -2x +6

x x +3
--------------------
12x^2 -6x 18
4x^3 -2x^2 +6x =
4x^3 8x^2 +0x +18
If -6 +6 =0 Why doesn't x -x =0

I really can't make sense of your post. What are you trying to do?
• Jan 20th 2009, 07:39 PM
Mush
Quote:

Originally Posted by Leona_Marie
4x^2 -2x +6

x x +3
--------------------
12x^2 -6x 18
4x^3 -2x^2 +6x =
4x^3 8x^2 +0x +18
If -6 +6 =0 Why doesn't x -x =0

Ahhh I see.

\$\displaystyle (x+3)(4x^2-2x+6) = x(4x^2-2x+6)+3(4x^2-2x+6) \$

\$\displaystyle = 4x^3-2x^2+6x+12x^2-6x+18 \$

\$\displaystyle = 4x^3+10x^2+18 \$

\$\displaystyle x - x \$ DOES equal zero :S.
• Jan 20th 2009, 07:55 PM
Leona_Marie
Quote:

Originally Posted by Mush
Ahhh I see.

\$\displaystyle (x+3)(4x^2-2x+6) = x(4x^2-2x+6)+3(4x^2-2x+6) \$

\$\displaystyle = 4x^3-2x^2+6x+12x^2-6x+18 \$

\$\displaystyle = 4x^3+10x^2+18 \$

\$\displaystyle x - x \$ DOES equal zero :S.

sorry thats not how I typed it. Im still learing my polys so when I do a problem then look at the answer sometimes they confuse me with bad answers... thats why I ask. thankyou